Povos indígenas no Brasil: subsunção manchada e insistência reprodutiva - Weslley Antonio Tadeu Monteiro Cantelmo (2023)
The insertion of capitalist relations in Brazil meant for indigenous peoples a new moment of war perpetrated by invaders. The greed for land and territory are important elements of Brazilian-style capitalist reproduction, in a movement of continuous expansion, especially since the Land Law of 1850. Thus, a new dynamic of interethnic relations and clash between different social forms and their mechanisms of reproduction was established. On one side, the totalizing and potentially homogenizing movement of Brazilian capitalism, with its institutional, epistemological, discursive and warlike aspects. On the other, a multiplicity of social forms originating from the continent, in direct and intense contact with the expansive dynamic of capital, seeking to establish what I have understood as reproductive insistence. From the perspective of the "white society", the role of the indigenous in the Brazilian capitalist project was to be incorporated, subsumed, as a workforce, rural or urban, under precarious conditions. However, an accurate analysis of history reveals that, despite the evident incorporations and disintegration of various peoples throughout the history of friction, even under very adverse conditions, indigenous social forms find ways to reproduce themselves, more or less intertwined with the surrounding social form and fundamentally pointing to a future. As a way of addressing this history of clash between indigenous social forms in Brazil and the capitalist social form, I seek to take stock of the trajectory of three peoples, through ethnographic and historical literature concerning them: the Tupinambá, the Huni Kuin and the Kaiowa. From a theoretical standpoint, I seek to develop the notions of stained subsunption and reproductive insistence, as a way of interpreting the historical dynamics that characterize the relationship of indigenous peoples with the surrounding capitalism.